Industry perspective, genetics and genomics of peanut blanchability - Shah, Priya; Wright, Graeme; Nwosu, Chigozie V.; O’Connor, Daniel; Satsos, Panagiota; Pasupuleti, Janila; Kona, Praveen; Singh, Kuldeep; Bera, Sandip K.; Thudi, Mahendar; Kole, Chittaranjan; Varshney, Rajeev K.; et al. (Elsevier, 2025)
Blanching is the process of removing the testa or seed coat (skin) from peanuts, and a genotype's capacity to release its testa is referred to as its blanchability. The genotype, seed quality, harvest date, level of maturity, as well as the length of time and temperature of the post-harvest storage period, all influence peanut's blanchability. This characteristic holds significant value in the production of food items made from peanuts. However, major research on this economically significant trait in breeding programmes has been limited. Blanchability is reported to be a highly heritable and genetically regulated trait, thus breeding and selection should be effective. Blanchability reports to be fixed in the early generations due to its relatively simple genetic control, hence choice of parents which have good blanchability is of utmost importance in a breeding programme. Since blanching percentage possess high genetic control with very low genotype × environment (G×E) interactions, effective selection for improved blanchability can be conducted in early generations. In peanut, blanchability is a great target trait for marker-assisted selection (MAS), but possess few factors that makes it difficult breeding target. These factors, include the high cost operations to measure blanchability and the relatively large seed size in particular, prevent testing in early generations. In this review, we emphasize genetic research on this trait, its relationship to other traits, factors influencing it, methods of measurement, its industrial significance, as well as initiatives and difficulties related to its improvement.